The Threat of Tomorrow: Impacts of Artificial Intelligence-Enhanced Cyber-attacks on International Relations - Esra Merve Çalışkan (Güvenlik Stratejileri Dergisi)
Artificial intelligence (AI) has revolutionized many sectors with its development, but it is also likely to pose new threats when used maliciously. This study examines the implications of state and nonstate actors using AI to conduct more sophisticated cyber-attacks and their potential consequences for international relations and global security. Cyber-attack detection has become more automated, targeted, and challenging due to rapid advances in AI. Thanks to AI, adversaries can now impersonate humans, manipulate data, eavesdrop on conversations, and exploit system weaknesses on an unprecedented scale. Unchecked, AI-enabled cyber-attacks can undermine diplomatic relations, increase the likelihood of military conflict between governments, and destabilize the economy. The international community will need new legal frameworks and technological measures to mitigate these risks. International cooperation is necessary to limit the development of AI cyber weapons, develop robust systems, and establish guidelines for responsible state activity in cyberspace. Through cooperation and foresight, the potential of AI is more likely to be achieved while reducing the likelihood of intensified cyber warfare. This paper provides a broad literature perspective and offers recommendations for both legal and technological solutions to reduce the likelihood of the effects of AI-based cyber-attacks.